(3HdhZ CbUi GdeQGe aj TQa GdYde heG jJYdb Hg ef GdCMcGes - (3eMeO Hf SYhO Hf CMeO GdZQfGWj GdYHGSj, CHh YHO Gddgs ((3eMeO Hf GdYHGS Hf jMj s)
(3ChdgG (B:s
(3hHYO aEf HYV GdCMHI eef NdU WdH efi s
(3BNQgG (B:s
(3NJe Gddg CYeGdfG HGdNjQGJ hhabfG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(483 (3O(B) s
Keywords: (3CUhd Gdabgs